The Influence Of Liquidity, Asset Growth, Activity Ratio, and Leverage On The Company-Going Concern - Wahyuni, Dhian; Nurramadhani, Rishma Nadya; Puspita Reswari, Brigita Ayu; Azzahra, Nabila; Budi Mahardika, I Putu Arya (Syntax Literate, 2023)
Profitability is an essential element to be able to maintain the company’s going concern. This study aims to determine the effect of liquidity, asset growth, leverage, and activity ratio on a company’s going concern proxied by Return on Asset (ROA), which is one of the profitability ratios. This study uses secondary data from the company's annual financial statements published by the Indonesia Stock Exchange (IDX). The population in this study is property and real estate companies listed on the IDX from 2017 to 2021. Furthermore, this study used a purposive sampling technique, resulting in 41 companies being used as research samples. Then the hypothesis is tested using Partial Least Square (PLS) analysis. The results of hypothesis testing show that liquidity and leverage have a negative and significant effect on the company's going concern. The ratio of activities has a positive and significant effect on the company's going concern. Meanwhile, asset growth has a positive and insignificant effect on the company's going concern.